2012
DOI: 10.1371/journal.pone.0032507
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Saccharomyces cerevisiae Strains Isolated from Different Grape Varieties and Winemaking Regions

Abstract: We herein evaluate intraspecific genetic diversity of fermentative vineyard-associated S. cerevisiae strains and evaluate relationships between grape varieties and geographical location on populational structures. From the musts obtained from 288 grape samples, collected from two wine regions (16 vineyards, nine grape varieties), 94 spontaneous fermentations were concluded and 2820 yeast isolates were obtained that belonged mainly (92%) to the species S. cerevisiae. Isolates were classified in 321 strains by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 49 publications
8
57
0
1
Order By: Relevance
“…A highly discriminating method based on 15 microsatellite markers specific to S. cerevisiae was used for molecular typing at the strain level. In comparison to previous studies based on other methods, such as PFGE, mtDNA RFLP, and inter-delta analysis (6,8,48), this S. cerevisiae ecological study used deep sampling and relied on the robustness of the microsatellite marker method (36,(49)(50)(51), performed with 15 loci as microsatellite markers and providing more sensitivity than previous studies. Multilocus microsatellite analysis allowed us to evaluate the genetic diversity of our population.…”
Section: Discussionmentioning
confidence: 99%
“…A highly discriminating method based on 15 microsatellite markers specific to S. cerevisiae was used for molecular typing at the strain level. In comparison to previous studies based on other methods, such as PFGE, mtDNA RFLP, and inter-delta analysis (6,8,48), this S. cerevisiae ecological study used deep sampling and relied on the robustness of the microsatellite marker method (36,(49)(50)(51), performed with 15 loci as microsatellite markers and providing more sensitivity than previous studies. Multilocus microsatellite analysis allowed us to evaluate the genetic diversity of our population.…”
Section: Discussionmentioning
confidence: 99%
“…Further DNA fingerprinting to the strain level revealed in this study that each fermentation typically harbors several different S. cerevisiae strains. While this phenomenon has been described intensively for wine fermentations (56,57), the intraspecific S. cerevisiae diversity in cocoa pulp fermentations is barely documented (7). We showed that one group of closely related strains was dominant in both fermentations and therefore selected a representative strain (Y927) as a potential starter culture and as a parental strain for further breeding experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This information was directly used to study the gene-based phenotypes, e.g., of sugar fermentations in yeast hybrids (108). The ease with which Saccharomyces strains can form viable hybrids results in hybrid formation also in natural environments (109)(110)(111)(112)(113). Based on the lack of apparent (or effective) prezygotic barriers, it has been proposed that speciation in Saccharomyces is ensured by postzygotic barriers preventing sporulation or the generation of viable spores.…”
Section: Yeast Hybrids Population Genomics and Reticulate Evolutionmentioning
confidence: 99%